2023
DOI: 10.1155/2023/4130937
|View full text |Cite
|
Sign up to set email alerts
|

δ‐Opioid Receptor Activation Inhibits Ferroptosis by Activating the Nrf2 Pathway in MPTP‐Induced Parkinson Disease Models

Abstract: Introduction. Recent studies suggest the involvement of ferroptosis in the pathogenesis of Parkinson disease (PD). δ-Opioid receptors (DORs) have neuroprotective effects in PD. It is not known whether the neuroprotective effects of DORs in PD are attributable to the inhibition of ferroptosis. Therefore, we aimed to investigate the role of DORs in ferroptosis in MPTP-induced PD models. Methods. To identify the influence of DORs on ferroptosis in MPTP-induced PD models, we measured the malondialdehyde (MDA) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“… 25 The NRF2 target genes not only regulate the key process of iron metabolism but also control the catabolism of foreign organisms and reactive aldehydes, as well as the synthesis of GSH and regeneration of nicotinamide adenine dinucleotide phosphate (NADPH), making it a versatile regulator of cellular resistance to iron degradation. 108 , 109 …”
Section: Regulation Of Intracellular Biochemical Processes On Ferropt...mentioning
confidence: 99%
“… 25 The NRF2 target genes not only regulate the key process of iron metabolism but also control the catabolism of foreign organisms and reactive aldehydes, as well as the synthesis of GSH and regeneration of nicotinamide adenine dinucleotide phosphate (NADPH), making it a versatile regulator of cellular resistance to iron degradation. 108 , 109 …”
Section: Regulation Of Intracellular Biochemical Processes On Ferropt...mentioning
confidence: 99%
“…We have previously reported that ORs (μ-, δ-, and κ-ORs) are present in microglia, and we observed that their activation could convert the LPS-induced proinflammatory subset of microglia into an anti-inflammatory subset by inhibiting the excessive production of nitric oxide, decreasing the expression of proinflammatory cytokines, and increasing the expression of anti-inflammatory molecules [ 22 ]. There is growing evidence that opioids may be neuroprotective under certain conditions [ 23 , 24 , 25 , 26 ]. In the present study, we investigated the mechanism underlying the antioxidant and anti-inflammatory effects of selected OR agonists (DAMGO, DADLE, and U-50488) in microglial cells.…”
Section: Introductionmentioning
confidence: 99%